Factors affecting the implementation of process based change. (1st January 2001) - Nash, Zoe; Childe, Steve; Maull, Roger
Failure is more common than success in the implementation of process based change. This paper looks at some reasons for failure drawn from implementation projects at IBM Product Support Services UK. PSS is primarily responsible for the maintenance of hardware and software and the selling of services associated with them. The research project focuses on process changes currently taking place within the division. The researchers were able to participate in process change projects and were able to use an approach based on action research. Three case studies of process based change were carried out. The first case study investigated the processes in the IBM Customer Support Centres. The second case study was a project to redesign service development processes. The third case study was about implementing a team working culture across PSS. In each of the three projects, there was a substantial analysis phase followed by disappointing results. One important factor was found to be organisational culture. The culture was often described as very "solutioning" based, where little time is spent on taking a "holistic" view or thoroughly examining the problem. The culture has also been described as "macho" where fixing a problem as quickly as possible is given the most credibility. Other factors which inhibited implementation included failures in project planning and management. There are also failures in process analysis, where departmental and functional boundaries restrict the work. There were several findings concerned with various human factors, such as failure to support user participation, team working and a lack of senior management commitment. Six problem themes arise. These are project planning and management, organisational culture, senior management commitment, analysis of problem situation, user involvement and human factors. The research project is currently testing these six elements in a framework to improve the implementation of process based change. This paper results from work done on a collaborative research project involving IBM Product Support and Services (PSS) and the University of Plymouth between September 1995 and January 1998.